Izkoriščanje sončne energije - Zidar, Mitja (Matrika, 2014)
This article is about the Sun as a source of energy in general but also presents some modern ways of harnessing solar radiation. The article focuses mainly on the physics behind the different techniques of harnessing solar energy. Among them are photovoltaic cells, heat collectors and solar sails.
Keywords: fotovoltaične celice; heat collectors; photovoltaic cells; solar energy; solar sails; Sonce; sončna energija; sončna jadra; Sun; toplotni zbiralniki